ANALISIS WACANA KRITIS TERHADAP ISU GENDER PEREMPUAN PADA SURAT KABAR HARIAN JAWA POS - Khusnul Irma Yanti; Roely Ardiansyah; Rini Damayanti (sarasvati, 2024)
This research describes women's gender issues in the Jawa Pos newspaper with the title “Critical Discourse Analysis of Women's Gender Issues in the Jawa Pos Daily Newspaper”. This research method uses a qualitative description with Sara Mills' Critical Discourse Analysis theory. The results of this study show gender issues in the news in the Jawa Pos daily newspaper. This study aims to describe (1) describe the role of women in the news in the Jawa Pos daily newspaper (2) describe the position of women when viewed from the position of the subject and object in the news in the Jawa Pos daily newspaper (3) describe the position of women when viewed in the position of the reader in the news in the Jawa Pos daily newspaper. The data collection techniques in this study used reading techniques, listening techniques, and note-taking techniques. In the written research, researchers found three issues of news about women in the Jawa Pos daily newspaper, namely (1) sexual harassment, (2) marginalization, (3) the role of women in politic